Dermatóglifos digitais e distribuição espacial dos Suruí, parque indígena Aripuana, Rondônia, análise estatística univariada - (:unkn) unknown (Museu Paraense Emílio Goeldi, 1990)
The goal of this paper is to discuss how the distribution of certain digital dematoglyphic traits of the Suruí indians from the State of Rondônia jvas influenccd by a recent process of population redistribution. It is argued that the fission process took place along family Unes, thus resulting in the genetic pool of the newly fonned villages not representing the variability found in the original villages. The results are interpreted in light of the action of random evolutiomry processes, notably the foundcr's effect.
Digital dermatoglyphics and spatial distribution of the Suruí, Aripuana Indigenous Park, Rondônia, univariate statistical analysis
Keywords: Dermatóglifos digitais; Sociedades indígenas; Suruí; Brasil; CNPQ::CIENCIAS BIOLOGICAS::ECOLOGIA